2021
DOI: 10.1007/s10943-021-01369-5
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Forgiveness and its Affective Correlates

Abstract: Although women are believed to be more forgiving than men, the results of many studies comparing women with men vary. Moreover, little is known about unique correlates or differential patterns of experiencing forgiveness by gender. In the present study, we compared men and women in terms of their level of dispositional forgiveness and its emotional correlates, namely positive and negative affect, anxiety, and emotional control. The sample consisted of 625 individuals aged 19–69, of whom 478 (76.5%) were women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 86 publications
0
7
2
Order By: Relevance
“…Most studies were conducted in the US and they did not provide for cross-cultural comparison. Meanwhile, recent research on a Polish sample ( Charzyńska, 2015 ; Kaleta and Mróz, 2021 ) showed, contrary to the expectations, a stronger tendency to forgive among male participants. Such results might be specific to the Polish sample or more universal in traditional European Christian countries (see Worthington 2019a ; Worthington et al., 2019 ; Zarzycka, 2019 ).…”
Section: Introductioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Most studies were conducted in the US and they did not provide for cross-cultural comparison. Meanwhile, recent research on a Polish sample ( Charzyńska, 2015 ; Kaleta and Mróz, 2021 ) showed, contrary to the expectations, a stronger tendency to forgive among male participants. Such results might be specific to the Polish sample or more universal in traditional European Christian countries (see Worthington 2019a ; Worthington et al., 2019 ; Zarzycka, 2019 ).…”
Section: Introductioncontrasting
confidence: 61%
“…We analyzed the results at an overall level, which does not reflect specific differences in forgiveness between gender and age groups. Although Kaleta and Mróz (2021) showed greater male forgivingness in the total score and in overcoming unforgiveness (negative dimension of forgiveness), there was no difference between genders in the positive dimension of forgivingness. Their findings revealed that dealing with unforgiving thoughts, emotions and behaviors after transgressions is easier for men than for women, but it is not easier for them to evoke positive states than it is for women.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Most studies were conducted in the US and they did not provide for cross-cultural comparison. Meanwhile, recent research on a Polish sample (Charzy nska, 2015;Kaleta and Mr oz, 2021) showed, contrary to the expectations, a stronger tendency to forgive among male participants. Such results might be specific to the Polish sample or more universal in traditional European Christian countries (see Worthington 2019a;Worthington et al, 2019;Zarzycka, 2019).…”
Section: Gender and Age Differences In Forgivenesscontrasting
confidence: 58%
“…Empowering women and elevating more women in leadership roles may lead to more societal forgiveness. Yet, it is not as straightforward as women being more forgiving than men as gender studies have found mixed results [38]. It is possible that it is related to a more holistic version of equality including not only gender, but racial, class, and other forms of equality as well.…”
Section: Author Detailsmentioning
confidence: 99%